SAS – SST simulations of the flow and heat transfer inside a square ribbed duct with artificial forcing - Zacharzewski, Piotr; Jefferson-Loveday, Richard J.; Morvan, Herve (2017)
Scale Resolving Simulations (SRS) are emerging as a promising compromise of cost and accuracy for industrial simulations of flows inside turbine blade cooling systems as they represent a necessary increase of accuracy with respect to Reynolds Averaged Navier Stokes (RANS) in the field. In this paper, several hybrid RANS-LES (Large Eddy Simulation) and SRS approaches are investigated. A Scale Adaptive Simulation (SAS) with spectrally calibrated artificial forcing is used to simulate flow inside a development section of a square duct with eight square equispaced ribs. Energy spectra, two-point correlations as well as other standard metrics are used to assess resolved content qualitatively as well as quantitatively. It is found that unmodified SST-SAS offers a marginal improvement over Unsteady RANS (URANS) for the present type of flow even on a LES-type grid and the solution is essentially steady. The artificial forcing used seems to trigger the resolving capability of the model and the solution is noticeably closer to experimental results while requiring minor extra computational demand. Effects of rotation are examined and it is found that the rotation appears to trigger the resolving mode of the unforced SAS model.